The promises of liberty : the history and contemporary relevance of the Thirteenth Amendment - Tsesis, Alexander (Columbia University Press, 2010)
In these original essays, America's leading historians and legal scholars reassess the ratification of the Thirteenth Amendment and its contemporary relevance to issues of liberty, justice, and equality. The Thirteenth Amendment abolished slavery in the United States, reasserting the radical, egalitarian dimensions of the Constitution. It laid the foundation for future civil rights and social justice legislation, yet subsequent reinterpretation and misappropriation has curbed more substantive change. With constitutional jurisprudence undergoing a revival, The Promises of Liberty provides a full portrait of the Thirteenth Amendment and its potential for ensuring liberty.